Risk Factors of Urogenital Problems among Perimenopausal Women - Suchithra, B. S.; Rajeev, T. P.; Dsilva, Fatima (Journal of Health and Allied Sciences NU, 2021)
Introduction Menopause is a natural event that results from cessation of the menstrual cycle. It usually occurs in midlife, marking the end of women’s reproductive life. Perimenopause refers to the time at which our body makes the natural transition to the menopause and may last for 4 to 8 years. A lot of urogenital problems start appearing after the age of 40 in women. The aim of the study is to identify the risk factors of the urogenital problems in perimenopausal women.Materials and Methods An explorative survey design with a purposive sampling method was used to collect the data from 200 women and older than 40 years admitted to the tertiary care hospital and a community under Natekal Primary Health Center were selected for the study.Results A total of 200 women were enrolled; 85 (42.5%) had urinary tract infections, 49 (24.5%) had urinary retention, 35 (17.5%) had vaginal dryness, 17 (8.5%) had urinary incontinence, 14 (7%) had a loss of libido. The majority, 76 (38%), had this problem for 1 to 2 years. There was association between selected demographic variables with risk factors like occupation (0.023; p < 0.05), number of children (0.023; p < 0.05), and mode of delivery (0.023; p < 0.05).Conclusion The study result concludes that there was a significant association between urogenital problems and risk factors.
Keywords: risk factors; urogenital problem; perimenopausal women